An electronic cigarette lithium ion battery

By using a mixed material of lithium manganese oxide and phosphate-manganese sodium iron stone as the positive electrode in electronic cigarette lithium-ion batteries and combining graphite and other materials as the negative electrode, the problem that existing batteries are difficult to meet high power requirements under large-scale discharge conditions is solved. , achieving high discharge voltage platform and low cost effect.

CN118040084BActive Publication Date: 2025-02-11广东比沃新能源股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410247449.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-05
Publication Date
2025-02-11
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

Existing electronic cigarette lithium-ion batteries are difficult to meet high power requirements under large-scale discharge conditions and are costly, especially the use of expensive lithium cobalt oxide or ternary materials.

Method used

The mixed material of lithium manganate and phosphate-manganese sodium iron stone is used as the positive electrode sheet, combined with graphite, hard carbon and other materials as the negative electrode sheet, and specific solvents and solutes are added to the electrolyte to improve the discharge voltage platform and large battery Current discharge capability.

Benefits of technology

It realizes the high discharge voltage platform and sufficient discharge capacity under high power discharge conditions, while effectively reducing battery costs and solving the problem of high cost of lithium cobalt oxide or ternary materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118040084B_ABST
    Figure CN118040084B_ABST
Patent Text Reader

Abstract

The present invention provides an electronic cigarette lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a shell container; wherein the material of the positive electrode sheet is a mixed material of lithium manganate and sodium phosphate manganese ore; the material of the negative electrode sheet is at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite; the shell container contains an electrolyte. The present invention uses the discharge oxidation state of sodium phosphate manganese ore as an additive for the positive electrode of lithium manganate, and mixes a certain proportion of lithium manganate and sodium phosphate manganese ore as the positive electrode of the battery. On the one hand, it can fully increase the discharge voltage of the electrode to meet most of the discharge capacity requirements of more than 3.3V, and on the other hand, it is suitable for large-diameter Na + Rapidly intercalated and deintercalated ion transport channels can provide a small radius of Li + It provides a faster transmission channel to meet large current discharge and solve the problem of extremely low voltage caused by instantaneous large current polarization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electronic cigarette lithium ion battery. Background Art

[0002] Lithium-ion batteries have been widely used as energy sources in electronic cigarette products because of their advantages such as small size, high energy density, good rate performance and flexible design. Because electronic cigarette batteries require a large discharge power and the discharge cut-off voltage is 3V, the battery is required to have a higher discharge voltage platform and a higher discharge capacity under high-rate discharge. At present, the capacity of lithium-ion batteries used in electronic cigarette batteries on the market is mostly distributed above 3.3V, and the positive poles of the batteries used mostly use highly conductive lithium cobalt oxide, ternary materials, or a mixture of the two. However, both lithium cobalt oxide and ternary materials contain low-abundance metal cobalt on the earth and are expensive. Lithium manganese oxide has the advantages of abundant resources and low prices, but under high-rate discharge conditions, with 3.0V as the cut-off, the capacity above 3.3V is low, which makes it difficult to meet the high-power discharge requirements of electronic cigarette batteries. Therefore, it is of great practical significance to develop lithium manganese oxide electronic cigarette batteries that still have a high discharge voltage platform under high-power discharge conditions and can ensure sufficient discharge capacity.

[0003] At present, the practical application requirements of available energy and high power of electronic cigarette lithium-ion batteries based on lithium cobalt oxide or ternary positive electrode materials are mainly improved by increasing the actual charging voltage or increasing the content of conductive additives. For example, the invention patent CN1121333848 discloses a ternary high-voltage electronic cigarette battery and its working method. On the one hand, the invention still uses ternary materials with expensive raw materials as the positive electrode material of the battery. On the other hand, through the battery structure design and increasing the high voltage of 4.35V of the battery to achieve most of the capacity above 3.3V, this solution still does not fundamentally solve the problems of high cost and low voltage, and even simply increasing the upper limit voltage of the ternary material charging to 4.35V may cause new safety problems.

[0004] Based on the above analysis, from the perspective of materials and battery core formula, it is urgent to develop corresponding technologies and products in order to fundamentally improve the conductivity of battery electrodes, achieve high-power discharge capability of batteries and maintain high discharge capacity, and effectively reduce battery costs. Summary of the invention

[0005] In view of this, the present invention proposes an electronic cigarette lithium ion battery to solve the problems existing in the above-mentioned prior art.

[0006] On the one hand, to achieve the above-mentioned purpose, the present invention proposes an electronic cigarette lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a shell container;

[0007] The material of the positive electrode sheet is a mixed material of lithium manganate and the oxidized phosphomanganese sodium iron ore;

[0008] The negative electrode sheet is made of at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite;

[0009] The outer shell container contains an electrolyte, and the electrolyte includes an electrolyte solvent, an electrolyte solute and an additive.

[0010] Optionally, the oxidized phosphomanganese sodium iron stone is Na z Fe 2-x (SO 4 ) 3 , where 0.15≤x≤0.3 and z<(2+2x).

[0011] Optionally, the mixing ratio of lithium manganate and sodium ferromanganese phosphate oxide in the positive electrode sheet is w:(1-w), wherein 50%≤w≤97%.

[0012] Optionally, the material of the negative electrode sheet also includes stable lithium metal powder, and the weight of the stable lithium metal powder in each negative electrode sheet is (total weight of sodium ferromagnetite oxidized phosphate in each positive electrode sheet × initial discharge capacity × 1.05-1.15) / 3623g.

[0013] Optionally, the electrolyte solvent is at least one of linear carbonates and fluorocarbonates thereof, cyclic carbonates and fluorocarbonates thereof, and ether-based solvents;

[0014] The electrolyte solute is at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium perchlorate.

[0015] On the other hand, to achieve the above-mentioned purpose, the present invention proposes a method for preparing an electronic cigarette lithium ion battery, comprising the following steps:

[0016] Step S1: In an inert atmosphere, take Na 2+2x Fe 2-x (SO 4 ) 3 Active Materials and NOBF 4 The mixture was placed in a container; acetonitrile was added to the container and stirred continuously, filtered, and the obtained powder was vacuum dried to collect the obtained Na z Fe 2-x (SO 4 ) 3 Powder, to obtain oxyphosphomanganese sodium iron stone;

[0017] Step S2: taking a small amount of sodium ferrophosphate oxide and calibrating the first discharge capacity;

[0018] Step S3: lithium manganate and the oxidized phosphomanganese sodium iron ore are weighed and mixed to obtain a mixed positive electrode material, the mixed positive electrode material is mixed with a conductive agent and a binder to prepare a slurry, and the slurry is coated to form a pole sheet to obtain a positive electrode sheet;

[0019] Step S4: mixing the negative electrode active material with a conductive agent, a binder and a dispersant to prepare a slurry, coating and forming an electrode sheet, and evenly adding stable lithium metal powder on the surface of the obtained electrode sheet to prepare a negative electrode sheet;

[0020] Step S5: The positive electrode sheet prepared in step S3 and the negative electrode sheet prepared in step S4 are blocked by a separator, and the positive electrode sheet, the separator and the negative electrode sheet are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet to obtain a winding core. After the winding core is added to the outer shell container, the electrolyte is injected, and sealing, primary pre-discharge, formation, exhaust, secondary sealing, and capacity separation are performed to obtain an electronic cigarette lithium-ion battery.

[0021] Optionally, in step S1: the Na 2+2x Fe 2-x (SO 4 ) 3 0.15≤x≤0.3; for every 1 mol of Na 2+ 2x Fe 2-x (SO 4 ) 3 4-20L acetonitrile was added; the stirring temperature was 25-50°C and the stirring time was 5-60h; the vacuum drying temperature was 80-85°C and the vacuum drying time was 4-12h, the Na z Fe 2-x (SO 4 ) 3 In the powder, z < (2 + 2x).

[0022] Optionally, in step S3: the mixing ratio of lithium manganate and sodium ferromagnetite is w:(1-w), wherein 50%≤w≤97%; the conductive agent is at least one of conductive carbon black, superconducting carbon black, carbon nanotubes, carbon fiber, and graphene; the ratio of the mixed positive electrode material, conductive agent, and binder is 94-97.5%:1.3-3%:1.2-3%.

[0023] Optionally, in step S4: the negative electrode active material is at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite; the weight of the stable lithium metal powder added to each negative electrode sheet is: (the total weight of sodium ferromagnetite oxide in each positive electrode sheet × the first discharge capacity × 1.05-1.15) / 3623g.

[0024] Optionally, in step S5, the lower limit voltage of the pre-discharge is 1.99V.

[0025] Compared with the prior art, the invention has the following advantages: 2 Fe 2 (SO 4 ) 3 (hereinafter referred to as NFS) discharge platform up to 3.8V, and has a large diameter Na + The advantage of the fast insertion and extraction ion transport channel is to use its discharge oxidation state Na z Fe 2-x (SO 4 ) 3 (hereinafter referred to as ONFS) as an additive for lithium manganese oxide positive electrode, a certain proportion of lithium manganese oxide and ONFS are mixed as the positive electrode of the battery. On the one hand, the discharge voltage of the electrode can be fully increased to meet most of the discharge capacity requirements above 3.3V. On the other hand, ONFS is suitable for large-diameter Na + Rapid insertion and extraction ion transport channels can provide a small radius Li + It provides a faster transmission channel to meet the high current discharge and solve the problem of extremely low voltage caused by instantaneous high current polarization. It can achieve high power discharge of the battery and ensure the capacity requirement when the discharge voltage is cut off at 3.0V. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0027] Figure 1 This is a schematic diagram of the preparation process of the electronic cigarette lithium ion battery of the present invention;

[0028] Figure 2 It is a comparison chart of 3C discharge curves of battery samples prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0029] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0030] This embodiment provides an electronic cigarette lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a shell container;

[0031] The material of the positive electrode sheet is a mixed material of lithium manganate and the oxidized phosphomanganese sodium iron ore;

[0032] The negative electrode sheet is made of at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite;

[0033] The outer shell container contains an electrolyte, and the electrolyte includes an electrolyte solvent, an electrolyte solute and an additive.

[0034] The preparation process of the electronic cigarette lithium ion battery proposed by the present invention is as follows Figure 1 As shown, including:

[0035] 1. Preparation of oxidized phosphomanganese sodium iron ore material

[0036] In an inert atmosphere, take the corresponding amount of Na 2+2x Fe 2-x (SO 4 ) 3 (0.15≤x≤0.3) Active materials and NOBF 4 , mixed and placed in a container; 2+2x Fe 2-x (SO 4 ) 3 Add the corresponding amount of acetonitrile to the container and stir continuously at 25-50°C for 5-60h; filter, place the obtained powder under vacuum drying at 80-85°C for 4-12h, collect the obtained powder, which is sodium ferrophosphate oxide, Na z Fe 2-x (SO 4 ) 3 (where z<2+2x) powder, marked as ONFS.

[0037] 2. Take a small amount of the obtained ONFS material and prepare it into ONFS / Li button battery, and calibrate the ONFS first discharge capacity C (ONFS) mAh / g.

[0038] 3. Preparation of mixed positive electrode sheet

[0039] According to the mass ratio of w:(1-w) (wherein 50%≤w≤97%), the corresponding lithium manganate and the sodium ferromanganese oxide phosphide ONFS obtained in 1 are weighed and mixed thoroughly to form a mixed positive electrode active material (marked as Mix-C). According to the ratio of Mix-C: conductive agent: binder = 94-97.5%: 1.3-3%: 1.2-3%, a positive electrode sheet is prepared.

[0040] The conductive agent is at least one of conductive carbon black, superconducting carbon black (SP), carbon nanotubes, carbon fibers, and graphene;

[0041] 4. Negative electrode preparation

[0042] The negative electrode active material, conductive agent, binder and dispersant are mixed in a certain proportion to form a slurry, coated and formed into a pole piece. Stable lithium metal powder (SLMP) is evenly added to the surface of the obtained negative electrode pole piece to make up for the lithium vacancies of the oxidized ONFS in the future, and the pole piece is fixed and formed by rolling to prepare the negative electrode pole piece.

[0043] The negative electrode active material is at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite;

[0044] The weight (g) of SLMP added to each negative electrode sheet is: (the total weight (g) of ONFS contained in each positive electrode sheet × C (ONFS) ×1.05-1.15) / 3623.

[0045] 5. Preparation of batteries

[0046] The positive electrode sheet prepared in 3 and the negative electrode sheet prepared in 4 are blocked with a separator in the middle, and the three are stacked and rolled into a core by lamination / winding. The core is placed in a container, and a lithium-ion battery product is obtained through the steps of injecting electrolyte, sealing, primary pre-discharge, formation, evacuation, secondary sealing, and capacity division.

[0047] The electrolyte is composed of an electrolyte solvent, an electrolyte solute and an additive, wherein the electrolyte solvent is at least one of a linear carbonate and a fluorocarbonate thereof, a cyclic carbonate and a fluorocarbonate thereof and an ether-based solvent; the electrolyte solute is at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate;

[0048] The primary pre-discharge lower limit voltage is not less than 1.99V.

[0049] In order to verify the outstanding advantages of the electronic cigarette lithium-ion battery of the present invention, different materials and preparation methods were used, and multiple embodiments and comparative examples were set. Finally, the performance parameters of the batteries prepared in the embodiments and comparative examples were summarized and analyzed, as follows:

[0050] Example 1

[0051] Weigh 500g Na 2.44 Fe 1.8 (SO 4 ) 3 and 475g NOBF 4 . In an inert atmosphere, Na 2.44 Fe 1.8 (SO 4 ) 3 Add 5L acetonitrile and stir continuously at 30℃, and continue to add NOBF 4 , keep the temperature constant, and continue stirring for 12 hours. Filter, wash with acetonitrile three times, and dry the obtained powder in a vacuum oven at 82°C and below 0.1 MPa for 6 hours. Collect the obtained powder and record it as ONFS1.

[0052] ONFS1 and lithium manganese oxide were mixed in a mass ratio of 1:1. The resulting mixed positive electrode material was recorded as ONFS1-LMO1. The positive electrode was prepared with ONFS1-LMO1, superconducting carbon black (SP), carbon nanotubes (CNT) and PVDF in a ratio of 97.5 parts, 1.2 parts, 0.6 parts and 1.2 parts. Graphite was used as the negative electrode active material to prepare the corresponding negative electrode sheet. SLMP was added at a ratio of 0.26g per electrode sheet, and the negative electrode sheet was prepared by rolling. After stacking the positive electrode sheet, the separator and the negative electrode sheet in order, they were wound in a winding manner to obtain a roll core, added to the shell container, and injected with 1M LiPF 6 Ethylene carbonate / diethyl carbonate / ethyl methyl carbonate electrolyte. The battery was discharged at a rate of 0.02C to a voltage of 1.99V. Then, formation, evacuation, secondary sealing and capacity separation were performed to prepare a high discharge voltage platform with a nominal capacity of 950mAh and a high rate 18350 battery cell. The battery cell is designated as ONFS1-L11. The battery cell ONFS1-L11 prepared in this embodiment was subjected to a discharge test, and its discharge curve is shown in the following figure. Figure 2 shown.

[0053] Example 2-Example 3

[0054] Example 2-Example 3, compared with Example 1, the only difference is that Na 2+2x Fe 2-x (SO 4 )3 The value of x in the molecular formula is different.

[0055] Example 2, x = 0.15, the structure of pyroxenite is Na 2 Fe 2 (SO 4 ) 3 The obtained battery cell is recorded as ONFS2-M11.

[0056] Example 3, x = 0.3, the structure of pyroxenite is Na 2.6 Fe 1.4 (SO 4 ) 3 The obtained battery cell is named ONFS3-M11.

[0057] Example 4-Example 6

[0058] Compared with Example 1, the only difference between Example 4 to Example 6 is that the mixing ratio of ONFS1 and lithium manganate is adjusted.

[0059] Example 4, compared with Example 1, is different only in that the mixing ratio of ONFS1 and lithium manganese oxide is adjusted to 3:7, and the obtained battery cell is marked as ONFS1-M37.

[0060] Example 5, compared with Example 1, is different only in that the mixing ratio of ONFS1 and lithium manganese oxide is adjusted to 2:8, and the obtained battery cell is marked as ONFS1-M28.

[0061] Example 6, compared with Example 1, is different only in that the mixing ratio of ONFS1 and lithium manganese oxide is adjusted to 1:9, and the obtained battery cell is marked as ONFS1-M19.

[0062] Example 7

[0063] The preparation process of ONFS1 is the same as that of Example 1.

[0064] ONFS1 and lithium manganese oxide were mixed in a mass ratio of 1:9. The resulting mixed positive electrode material was recorded as ONFS1-LMO9. The positive electrode was prepared with ONFS1-LMO9, superconducting carbon black (SP), carbon nanotubes (CNT) and PVDF in a ratio of 95 parts, 1.5 parts, 1.0 parts and 2.5 parts. Graphite was used as the negative electrode active material to prepare the corresponding negative electrode sheet. SLMP was added at a ratio of 0.03g per electrode sheet, and the negative electrode sheet was prepared by rolling. After stacking the positive electrode sheet, the separator and the negative electrode sheet in order, they were wound in a winding manner to obtain a core, added to the shell container, and injected with 1.2M LiPF 6Ethylene carbonate / ethyl methyl carbonate electrolyte. The battery was discharged at a rate of 0.02C to a voltage of 1.99V. Then, formation, evacuation, secondary sealing and capacity separation were performed to prepare a high discharge voltage platform with a nominal capacity of 950mAh and a high rate 18350 battery cell. The battery cell is designated as ONFS1-M19-C.

[0065] Example 8

[0066] The preparation process of ONFS1 is the same as that of Example 1.

[0067] ONFS1 and lithium manganese oxide were mixed in a mass ratio of 1:9. The resulting mixed positive electrode material was recorded as ONFS1-LMO9. The positive electrode was prepared with ONFS1-LMO9, superconducting carbon black (SP), carbon nanotubes (CNT) and PVDF in a ratio of 95 parts, 1.5 parts, 1.0 parts and 2.5 parts. The graphite-hard carbon composite material was used as the negative electrode active material to prepare the corresponding negative electrode sheet. SLMP was added at a ratio of 0.26g per electrode sheet, and the negative electrode sheet was prepared by rolling. After stacking the positive electrode sheet, the separator and the negative electrode sheet in order, they were wound in a winding manner to obtain a core, added to the shell container, and injected with 1.0M LiPF 6 Ethylene carbonate / ethyl methyl carbonate / tetrahydrofuran electrolyte. The battery was discharged at a rate of 0.02C to a voltage of 1.99V. Then, formation, evacuation, secondary sealing and capacity separation were performed to prepare a high discharge voltage platform with a nominal capacity of 950mAh and a high rate 18350 battery cell. The battery cell is designated as ONFS1-M19-HC.

[0068] Comparative Example 1

[0069] Lithium manganate, superconducting carbon black (SP), carbon nanotubes (CNT) and PVDF were weighed in the proportions of 97.5 parts, 1.2 parts, 0.6 parts and 1.2 parts respectively to prepare the positive electrode. Graphite was used as the negative electrode active material to prepare the corresponding negative electrode sheet. The positive electrode sheet, separator and negative electrode sheet were stacked in order, and then wound in a winding manner to obtain a core, which was added to the outer shell container and injected with 1M LiPF 6 Ethylene carbonate / diethyl carbonate / ethyl methyl carbonate electrolyte. Then, formation, degassing, secondary sealing and capacity separation were performed to prepare a pure lithium manganese oxide 18350 battery cell with a nominal capacity of 950 mAh. The battery cell is recorded as Blank.

[0070] The performance comparison of each embodiment product is shown in Table 1:

[0071] Table 1

[0072] (Discharge cut-off voltage 3V)

[0073]

[0074]

[0075] By analyzing the performance results of the batteries obtained in the above-mentioned embodiments and comparative examples, it can be seen that:

[0076] In the battery cell samples prepared by the present invention, the battery cell capacity and discharge capacity are both stable above 950mAh. The capacity of the ONFS1-M19-C battery cell prepared in Example 7 reaches 1052mAh, and the discharge capacity reaches 1028mAh. At the same time, the capacity retention rate of the battery cell samples of the present invention is stable above 95%, and the discharge median voltage is much greater than 3.3V. The discharge capacity of Example 1 is also above 950mAh, and it has the highest 3C discharge voltage platform of 3.6304V. The Blank battery cell prepared in Comparative Example 1 is smaller than the battery cell prepared in this aspect in terms of discharge capacity, capacity retention rate and discharge median voltage. Its discharge platform is low, which is 3.3200V, and its capacity at 3C discharge rate is only 828mAh, and the capacity retention rate relative to 1C discharge capacity is only 82.00%. It can be seen from this that the lithium ion battery prepared by the present invention has significant advantages over traditional lithium batteries in terms of discharge voltage, and meets large current discharge, solving the problem of extremely low voltage caused by instantaneous large current polarization.

[0077] The present invention is based on sodium phosphate manganese iron stone Na with a high discharge voltage platform. 2 Fe 2 (SO 4 ) 3 The discharge platform is as high as 3.8V, and it can provide large diameter Na + The advantage of the fast insertion and extraction ion transport channel is to use its discharge oxidation state Na z Fe 2-x (SO 4 ) 3 As an additive for lithium manganese oxide positive electrode, a certain proportion of lithium manganese oxide and ONFS are mixed as the positive electrode of the battery. On the one hand, the discharge voltage of the electrode can be fully increased to meet the needs of most discharge capacities above 3.3V. On the other hand, ONFS is suitable for large-diameter Na + Rapid insertion and extraction ion transport channels can provide a small radius Li + It provides a faster transmission channel to meet the high current discharge and solve the problem of extremely low voltage caused by instantaneous high current polarization. It can achieve high power discharge of the battery and ensure the capacity requirement when the discharge voltage is cut off at 3.0V.

[0078] For the numerical ranges in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the range.

[0079] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, those skilled in the art should understand that any person skilled in the art can still modify the technical solutions described in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or perform equivalent replacements on some of the technical features thereof; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. They should all be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. An electronic cigarette lithium-ion battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and a shell container; The material of the positive electrode sheet is a mixed material of lithium manganate and sodium iron phosphate manganese oxide; The negative electrode sheet is made of at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite; The outer shell container contains an electrolyte, and the electrolyte includes an electrolyte solvent, an electrolyte solute and an additive; The oxidized phosphomanganese sodium iron stone is Na z Fe 2-x (SO4)3, where 0.15≤x≤0.3 and z<(2+2x).

2. The electronic cigarette lithium-ion battery according to claim 1, characterized in that: The mixing ratio of lithium manganate and sodium ferromanganese oxide in the positive electrode sheet is w:(1-w), wherein 50%≤w≤97%.

3. The electronic cigarette lithium-ion battery according to claim 1, characterized in that: The material of the negative electrode sheet also includes stable lithium metal powder, and the weight of the stable lithium metal powder in each negative electrode sheet is (the total weight of sodium ferromagnetite oxidized phosphate manganese in each positive electrode sheet×the first discharge capacity×1.05-1.15) / 3623g.

4. The electronic cigarette lithium-ion battery according to claim 1, characterized in that: The electrolyte solvent is at least one of linear carbonates and fluorocarbonates thereof, cyclic carbonates and fluorocarbonates thereof, and ether-based solvents; The electrolyte solute is at least one of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium perchlorate.

5. A method for preparing an electronic cigarette lithium-ion battery, characterized in that: include: Step S1: In an inert atmosphere, take Na 2+2x Fe 2-x The (SO4)3 active material and NOBF4 were mixed and placed in a container; acetonitrile was added to the container and stirred and filtered continuously, and the obtained powder was vacuum dried to collect the obtained Na z Fe 2-x (SO4)3 powder, to obtain oxyphosphorus manganese sodium iron stone; The Na 2+2x Fe 2-x 0.15≤x≤0.3 in (SO4)3; The Na z Fe 2-x z<(2+2x) in (SO4)3 powder; Step S2: taking a small amount of sodium ferrophosphate oxide and calibrating the first discharge capacity; Step S3: lithium manganate and the oxidized phosphomanganese sodium iron ore are weighed and mixed to obtain a mixed positive electrode material, the mixed positive electrode material is mixed with a conductive agent and a binder to prepare a slurry, and the slurry is coated to form a pole sheet to obtain a positive electrode sheet; Step S4: mixing the negative electrode active material with a conductive agent, a binder and a dispersant to prepare a slurry, coating and forming an electrode sheet, and evenly adding stable lithium metal powder on the surface of the obtained electrode sheet to prepare a negative electrode sheet; Step S5: The positive electrode sheet prepared in step S3 and the negative electrode sheet prepared in step S4 are blocked by a separator, and the positive electrode sheet, the separator and the negative electrode sheet are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet to obtain a winding core. After the winding core is added to the outer shell container, the electrolyte is injected, and sealing, primary pre-discharge, formation, exhaust, secondary sealing, and capacity separation are performed to obtain an electronic cigarette lithium-ion battery.

6. The method for preparing an electronic cigarette lithium-ion battery according to claim 5, characterized in that: In step S1: for every 1 mol of Na 2+2x Fe 2-x Add 4-20L acetonitrile to (SO4)3; keep stirring at a temperature of 25-50°C and a stirring time of 5-60h; and vacuum drying at a temperature of 80-85°C and a vacuum drying time of 4-12h.

7. The method for preparing an electronic cigarette lithium-ion battery according to claim 5, characterized in that: In the step S3: the mixing ratio of lithium manganate and sodium ferromagnetite is w:(1-w), wherein 50%≤w≤97%; the conductive agent is at least one of conductive carbon black, superconducting carbon black, carbon nanotubes, carbon fiber, and graphene; the ratio of the mixed positive electrode material, conductive agent, and binder is 94-97.5%:1.3-3%:1.2-3%.

8. The method for preparing an electronic cigarette lithium-ion battery according to claim 5, characterized in that: In the step S4: the negative electrode active material is at least one of graphite, hard carbon, soft carbon, silicon, silicon-carbon composite, tin and tin-containing composite; the weight of the stable lithium metal powder added to each negative electrode sheet is: (the total weight of oxyphosphomanganese sodium iron ore in each positive electrode sheet × the first discharge capacity × 1.05-1.15) / 3623g.

9. The method for preparing an electronic cigarette lithium-ion battery according to claim 5, characterized in that: In the step S5, the lower limit voltage of the pre-discharge is 1.99V.

Citation Information

Patent Citations

  • Water-soluble lithium ion battery

    CN102496746A

  • Sodium-ion battery positive pole Na2+2xFe2-x(SO4)3@ carbon composite material and preparing method thereof

    CN105355886A